Managing Human Resources for Surge Capacity in Referral Hospitals Based on WHO Hospital Readiness Checklist for Covid-19 - Fitri Dinia; Laksono Trisnantoro; Mochamat Helmi (Folia Medica Indonesiana, 2022)
Highlights: